Application of cDNA microarray in halal research - Salleh, Faqihah; Hashim, Yumi Zuhanis Has-Yun; Ramli, Noriah; Salleh, Sheikh Ibrahim (IIUM Press, 2015)
cDNA Microarray is a powerful tool of technology to study gene expression. The technique allows simultaneous analysis on thousands of gene expression in a single assay compared to traditional molecular biology tools which generally allow only single gene expression at a time. This high throughput technology has been applied in diversified researches such as in toxicology, human nutrition, environmental, clinical diagnoses and many more. To the best of our knowledge, the technique has not been widely applied in Halal research although studies on the effects of consumption of alcohol and toxic compounds to human from the medical perspective and safety have been reported. This review sets to look at the feasibility of the cDNA Microarray technology in Halal research with a case study on the effects of alcohol intake on gene expression as precedent of the promising technology in deciphering the effects of Halal versus Haram components particularly from animals to human cells.